Aplikasi Pencarian Rute Perguruan Tinggi Berbasis Android Menggunakan Location Based Service (LBS) di Kota Semarang - Satriaji Cahyo Nugroho; Oky Dwi Nurhayati; Eko Didik Widianto (Jurnal Teknologi dan Sistem Komputer, 2015)
The University is an institution that has a role and strategic position in the achievement of educational goals. Semarang, as the center of Central Java has many universities, both public and private. The obstacles are that many students like high school kids who want to go to university do not know the location and any information contained on the university they want. Therefore, along with the development of mobile devices, which is based on Android Smartphone then made an application that can be easily used in the search of location and information about the university. The applications created is an android based applications using the Waterfall method which has five stages in sequence. Those are Needs Analysis, System Design, Coding, Testing, and Maintenance. Testing applications using the Black-box test and tested on the users. The Results of this application design is an application that is called "University Route Searching Application Using Location Based Service (LBS) in Semarang. This application can meet the needs of users in determining the route toward college that will be addressed.